Pengetahuan Dan Sikap Tentang Berhenti Merokok Pada Perokok Aktif Di Kelurahan Ketintang Surabaya: Mix-Method - Putri, Putu Melista; Pratama, Anggara Martha; Juwariya, Firdayatul; Raharjo, Dian Natasya; Lorensia, Amelia (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2023)
The prevalence of smoking in adolescents has increased from year to year. Smoker awareness is very important inincreasing the success of quitting smoking. The level of knowledge and attitudes is needed for self-managementattitudes for smokers. The aim of this study was to determine the level of knowledge and attitudes about smokingcessation among active smokers in the Ketintang Village, Surabaya. The design that will be used in this study isMix-Methods with Convergent Parallel Design. This research was conducted in Ketintang, Surabaya, with theconsideration of the availability of active smokers in a Mosque Youth and Youth Organization organization, whichwas carried out for 2 months starting April 2022 - June 2022. The variables measured in this study included thelevel of knowledge and attitudes of active smokers about quitting smoking. Data collection was carried out by indepth interviews and data were analyzed descriptively. Respondents involved in the study were 40 people. Theaverage respondent has good knowledge (90.00%) and a positive attitude (95.00%). Respondents thought that thetypes of cigarettes according to respondents were ordinary cigarettes (conventional), shisya, and vape. Respondentsthought that the way to quit smoking could be done by making an independent effort to quit, avoiding smokers'surroundings, and replacing conventional cigarettes with electric cigarettes (vape). Therefore, smoking cessationprograms need to be improved, especially for smokers who wish to quit smoking.